Nido, huevos, pichón y comportamiento reproductivo de la Saracura (Aramides saracura) en Argentina - Di Sallo, Facundo G.; Bodrati, Alejandro (Nuestras Aves, 2015)
Este artículo no cuenta con un resumen.